THE Multimodality Practices in Hearing Impairment EFL Classroom - Bunga Ikasari; Nur Arifah Drajati; Sumardi Sumardi (IJER (Indonesian Journal of Educational Research), 2019)
Abstract This article provides a report of teacher’s experience in using ICT-integrated multimodal texts to help heard-of-hearing learners develop or improve their literacy skills especially in mastering reading comprehension. Additionally, this study tried to investigate the impacts of the use of the materials on students’ learning. The study was carried out in a special need school. The research is a case study of an English teacher and three hard-of-hearing learners. The material consists of video observation, photographs, field notes, documents, and interviews with the teacher and the students. The findings showed that multimodal texts which were built with diverse modes or semiotic resources such as color, sound, motion, written text, and gesture could ease the teacher to help the students perform better in the area of reading comprehension although she also encountered some challenges. Moreover, the students perceived the use of multimodal texts positively as it allowed them to participate more actively in the classroom activities. I believe that the result of the study can serve as a consideration for English teachers in teaching readings to hard hearing learners. Keyword: Hard hearing learners, multimodal texts, reading for hard hearing